e-서비스 품질 평가모형을 이용한 전자책 서비스 이용자 만족도 연구 - 김동은(Dong Eun Kim); 안나연(Nah-Yeon Ahn); 이경률(Kyoung-Ryul Lee) (한국콘텐츠학회 논문지, 14(7), 2014)
The purpose of this study is to derive the suggestion of satisfaction of e-book services on the basis of the recent literature on quality assessment for e-service which have been mainly studied on library realm. For this purpose, This study added post-management service which is applicable to measure satisfaction of e-book services based on E-S-Qual and Libqual. We expand our scope of service to using of e-book content and services for individual customers, and analyzed the relationship between satisfaction with the system, the content, the after-sale service. On this foundation, existing e-book service companies can offer their services more efficiently, thereby making the e-book content more diverse, along with developing specialized e-book service to increasing their customer's satisfaction. In addition, the latest and diversity is important as well. Moreover, performing rapid post-management services after the sale of the product or service, can be important variables for customer satisfaction. Therefore, not only the system and content, providing required level post-management services by customers can satisfy the existing customers and create new customers. 본 연구는 기존의 e-서비스 품질 평가에 관한 최근 문헌을 토대로 도서관 위주의 연구에만 국한된 전자책 서비스 품질 연구를 발전시켜, 개인 고객의 전자책 콘텐츠 서비스 이용을 중심으로 시스템, 콘텐츠, 사후관리 서비스에 따른 만족도와의 관계를 분석하고자 하였다. 이를 위해 e-서비스 품질 평가 모형과 도서관서비스 품질평가 연구모형을 바탕으로 전자책 서비스 이용자 만족도 측정에 있어 중요한 요소로 작용 가능한 사후 관리 서비스 요인을 추가하였다. 기존의 전자책 서비스 기업들이 보다 효율적으로 서비스를 제공하고 나아가 서비스의 만족도를 높이기 위해서는 좀 더 다양한 콘텐츠의 제공과 함께 전자책에 특화된 서비스의 개발 및 다양성과 최신성이 확보된 콘텐츠가 요구된다. 더불어 제품 서비스 판매 이후 이루어지는 신속한 사후관리 서비스는 고객만족을 위한 중요한 변수가 될 수 있다. 따라서 콘텐츠 시스템뿐만 아니라, 고객이 원하는 수준의 사후 관리 서비스의 제공을 통해 기존 고객을 만족 시키고 신규 고객을 창출할 수 있다.